DIGITAL TRANSFORMATION IN HR: IMPACTS OF AUTOMATION AND ARTIFICIAL INTELLIGENCE ON THE EMPLOYEE EXPERIENCE (International Seven Journal of Multidisciplinary, 2024)
The digital transformation in the human resources sector represents a milestone in the reconfiguration of people management practices, incorporating automation and artificial intelligence as strategic elements to optimize processes, increase efficiency, and improve the employee experience. This study aimed to analyze the impacts of these technologies on the dynamics of work and the perceptions of professionals, highlighting both the benefits and challenges associated with their implementation. The investigation, conducted through bibliographic research, allowed to identify that the integration of digital tools enables greater assertiveness in recruitment and selection, personalization in the development of skills and increased agility in internal processes. In addition, it was found that such advances can strengthen engagement and talent retention, as long as they are accompanied by change management policies and digital inclusion strategies. On the other hand, barriers such as cultural resistance, the need for continuous training, and concerns about data security and privacy were identified. It is concluded that digital transformation in HR, when conducted in a planned, inclusive and aligned manner with corporate values, is capable of generating substantial gains for the organization and its employees, consolidating itself as a strategic path for companies that seek innovation and sustainability in the contemporary competitive scenario.